2008
DOI: 10.1089/ten.tec.2008.0168
|View full text |Cite
|
Sign up to set email alerts
|

Non-Viral Delivery of the Gene for Glial Cell Line-Derived Neurotrophic Factor to Mesenchymal Stem Cells In Vitro Via a Collagen Scaffold

Abstract: Recent advances in tissue engineering that combine an extracellular matrix-like scaffold with therapeutic molecules, cells, DNA encoding therapeutic proteins, or a combination of the three hold promise for treating defects in the brain resulting from a penetrating injury or tumor resection. The purpose of this study was to investigate a porous sponge-like collagen scaffold for non-viral delivery of a plasmid encoding for glial cell line-derived neurotrophic factor (pGDNF) to rat marrow stromal stem cells (also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…During the last 10 years several authors have reported promising results regarding the use of cationic lipids (Bolliet et al, 2008), polymers , dendrimers (Santos et al, 2009) and different electroporation techniques (Aluigi et al, 2006;Ferreira et al, 2008) to deliver plasmid DNA (pDNA) into MSC derived from BM, cord blood or adipose tissue. When compared to other non-viral methods, conventional electroporation has led to higher transfection efficiencies to MSC although encompassed with high cellular mortality, which might be due to the high electrode surface area (Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…During the last 10 years several authors have reported promising results regarding the use of cationic lipids (Bolliet et al, 2008), polymers , dendrimers (Santos et al, 2009) and different electroporation techniques (Aluigi et al, 2006;Ferreira et al, 2008) to deliver plasmid DNA (pDNA) into MSC derived from BM, cord blood or adipose tissue. When compared to other non-viral methods, conventional electroporation has led to higher transfection efficiencies to MSC although encompassed with high cellular mortality, which might be due to the high electrode surface area (Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Cell Culture and Transfection: Rat MSCs were harvested from both the femurs and tibiae of 6 young Lewis rats (<6 weeks old) as previously described [62]. The cells from the 6 rats were cultured separately throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Collagen's inherent integrin binding sites are advantageous as they promote the migration and differentiation of neuronal cells (Bradshaw et al, 1995). Modification of collagen scaffolds via the addition of neurotrophic factors (Han et al, 2009;Houweling et al, 1998), other pharmacologically active substances (Bolliet et al, 2008), or cells ( Joosten et al, 2004) has been described to increase axonal regeneration and functional recovery after spinal cord trauma. Despite the fact that collagen per se is a suitable substrate for neuronal growth, it is also important to consider the role of collagen as the basement membrane constituent of the lesion scar that develops after a traumatic CNS injury (Fawcett et al, 2012;Klapka and Muller, 2006).…”
Section: Collagenmentioning
confidence: 99%